The complete guide to futures trading : what you need to know about the risks and rewards (J. Wiley & Sons, 2005)
PRAISE FOR The Complete Guide to FUTURES TRADING"It does a good job of conveying, in a style that is clear to the layman, how the futures world works and what is required to succeed as a trader."--Financial Engineering News"This landmark book makes futures trading accessible to mainstream individual investors.